2018
DOI: 10.3390/molecules23071716
|View full text |Cite
|
Sign up to set email alerts
|

Application of Spray Drying Particle Engineering to a High-Functionality/Low-Solubility Milk Thistle Extract: Powders Production and Characterization

Abstract: Many natural compounds having antioxidant and anti-inflammatory activity are a potential target for new therapies against chronic inflammatory syndromes. The oral administration of functional herbal supplements may become a prevention strategy or therapy adjuvant for susceptible patients. A case study is our milk thistle (Silybum marianum) extract rich in silymarin complex. A water-soluble microencapsulated powder system was developed by a spray drying technique to improve the poor silymarin bioactivity after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…The results of the MTT test (Table 3) showed that the inhibitory effect of Batch-15 (AEC% 3.9%, w/w) remained unchanged for SK-Mel-28 (IC 50 10.550 mg/mL containing 0.411 mg/mL of HSE) or resulted in improved for A375 and HeLa (IC 50 4.550 and 8.070 mg/mL, containing 0.177 and 0.315 mg/mL of HSE, respectively), proving as the spray drying process did not affect HSE efficacy. On the contrary, the produced amorphous microsystems were able to improve the wettability of HSE and the release of HSE active components in water cellular environmental [13]. Moreover, the occurrence of proline in the multi-polymeric Batch-15 matrix will affect the cytotoxic properties of the HSE raw extract.…”
Section: Functional Activity Of Batch-15mentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the MTT test (Table 3) showed that the inhibitory effect of Batch-15 (AEC% 3.9%, w/w) remained unchanged for SK-Mel-28 (IC 50 10.550 mg/mL containing 0.411 mg/mL of HSE) or resulted in improved for A375 and HeLa (IC 50 4.550 and 8.070 mg/mL, containing 0.177 and 0.315 mg/mL of HSE, respectively), proving as the spray drying process did not affect HSE efficacy. On the contrary, the produced amorphous microsystems were able to improve the wettability of HSE and the release of HSE active components in water cellular environmental [13]. Moreover, the occurrence of proline in the multi-polymeric Batch-15 matrix will affect the cytotoxic properties of the HSE raw extract.…”
Section: Functional Activity Of Batch-15mentioning
confidence: 99%
“…More than 45 pilot experiments (blank and loaded powders, Table 1) were carried out to find the optimum of liquid feed in terms of polymer concentrations and weight polymer ratios with respect to the process yields, loading ability, and resultant powders technological characteristics. As an example, only three batches (3,9,12) of blank powders and two batches of loaded (13,15) ones have been selected, discussed in the text, and reported in the Table 1 as demonstrative samples of the taken experimental steps. Additional information was included in the Supplementary Materials.…”
Section: Microencapsulation Process Morphological and Dimensional Cmentioning
confidence: 99%
See 3 more Smart Citations